2009
DOI: 10.1136/ard.2008.105775
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and cartilage-protecting effects of an intra-articularly injected anti-TNFα single-chain Fv antibody (ESBA105) designed for local therapeutic use

Abstract: ESBA105 potently inhibits inflammation and prevents cartilage damage triggered by TNFalpha. In contrast to a full length IgG, ESBA105 also penetrates into cartilage and can be expected to reverse the TNFalpha-induced catabolic state of articular cartilage in arthritides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…Such an alteration is primarily associated with the complex network of interactions among inflammatory factors, resulting in synovial inflammation and chondrocytic disturbance (18,19). As one of the key inflammatory factors responsible for the articular cartilage degeneration, TNF-· is involved in the synovial inflammatory response, the initiation of chondrocytic apoptosis, the imbalance between chondral damage and repairs and the eventual acceleration of articular cartilage degeneration (20). In order to study the effects of millimeter wave treatment on TNF-·-induced cell death, we established chondrocyte culture in vitro by using stepwise 0.2% collagenase type II digestion and then we treated the chondrocytes with 0, 10, 20 and 40 ng/ml TNF-· for 2, 4 and 8 h. As expected, we found an evident decreasing trend in the activities of chondrocytes by MTT assay with time and TNF-· dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Such an alteration is primarily associated with the complex network of interactions among inflammatory factors, resulting in synovial inflammation and chondrocytic disturbance (18,19). As one of the key inflammatory factors responsible for the articular cartilage degeneration, TNF-· is involved in the synovial inflammatory response, the initiation of chondrocytic apoptosis, the imbalance between chondral damage and repairs and the eventual acceleration of articular cartilage degeneration (20). In order to study the effects of millimeter wave treatment on TNF-·-induced cell death, we established chondrocyte culture in vitro by using stepwise 0.2% collagenase type II digestion and then we treated the chondrocytes with 0, 10, 20 and 40 ng/ml TNF-· for 2, 4 and 8 h. As expected, we found an evident decreasing trend in the activities of chondrocytes by MTT assay with time and TNF-· dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The grades were summed to obtain an arthritis index (ranging from 0 to 8) (21). TB-stained slides were used to estimate joint proteoglycan content, as described previously (22). Images of the joint surface of each sample were digitalized and evaluated using Image J software (National Institutes of Health, Bethesda, MD).…”
Section: Knee Joint Evaluationmentioning
confidence: 99%
“…Changlong Y et al found that NF-B p65-speciWc siRNA inhibited the expression of COX-2, NOS-2, and MMP-9 induced by TNF in vitro and in vivo research [13,14]. However, they didn't pay attention to whether the chondrocytes or synovial cells exerted apoptosis 2 weeks after stimulation.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the important role of TNF in OA, there were dozens of studies targeting inhibition of TNF trying to slow down or halt disease progression. They indeed yielded some beneWts on relieving articular swelling and inhibiting cartilage damage triggered by TNF in the rat model [14]. Nuclear factor-kappa B (NF-B), one of the TNF downstream factors, was also considered as an OA therapy target and down-regulated to relieve articular inXammation and bone erosion [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%